ARISAN EMAS PERSFEKTIF FIQH MUAMALAH (Studi di Jorong Koto Gadang Nagari Simawang Kecamatan Rambatan Kabupaten Tanah Datar) - Kurnia Ramanda Ilahi; Nailur Rahmi (Jurnal Integrasi Ilmu Syariah (Jisrah), 2021)
This study examines the implementation of the gold gathering in Jorong Koto Gadang Nagari Simawang, Rambat District, Tanah Datar Regency in the Perspective of Fiqh Muamalah. The problem in this research is how to implement the Arisan Emas in Jorong Koto Gadang Nagari Simawang, Rambat District, Tanah Datar Regency. What are the contracts used in the implementation of this Arisan and how is the view of muamalah fiqh on the implementation of the Gold Arisan in Jorong Koto Gadang Nagari Simawang, Rambat District, Tanah Datar Regency.The research method that I use in this research is field research. While the nature of the research is qualitative descriptive, qualitative descriptive research is describing the phenomena that occur in the field as they are according to reality. As the main data source, namely people involved in the implementation of the gold gathering in Simawang Village, and as a source of data obtained include primary and secondary data, primary data sources consisting of the head of the gold arisan and 9 participants of the gold gathering while secondary data sources were obtained through a number of books, journals, articles and other reading sources to strengthen primary data. Data collection was carried out using interview and observation techniques.Based on the results of the research that the authors have done, it can be concluded that the implementation of Asrisanemas in Jorong Koto Gadang Nagari Simawang, Rambat District, Tanah Datar Regency is to use the ijarah contract and accounts payable agreement, the payment system is through the membership fees of the gold arisan, fixing the gold price according to the current gold price and giving for the chairman of the Arisan only voluntarily. In the view of fiqh muamalah, the implementation of the gold gathering that took place in Jorong Koto Gadang Nagari Simawang, Rambat Subdistrict, Tanah Datar Regency, Arisan like this is unacceptable because there is no certainty and is detrimental to one of the parties with a shortage and overpayment which is commonly referred to as usury and giving money. To the head of the arisan is a voluntary fee, the voluntary money given to the head of the arisan is considered a wage because the provisions of the muamalah for each job in muamalah are required to have a wage.